2016
DOI: 10.1098/rsif.2016.0228
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian phospholipid homeostasis: evidence that membrane curvature elastic stress drives homeoviscous adaptation in vivo

Abstract: Several theories of phospholipid homeostasis have postulated that cells regulate the molecular composition of their bilayer membranes, such that a common biophysical membrane parameter is under homeostatic control. Two commonly cited theories are the intrinsic curvature hypothesis, which states that cells control membrane curvature elastic stress, and the theory of homeoviscous adaptation, which postulates cells control acyl chain packing order (membrane order). In this paper, we present evidence from datadriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…For example, curvature elastic stress, which arises from a system being forced to adopt a curvature that is different from c 0 , has been shown to modulate the activity of many membrane interacting proteins 3,4 and drives the folding of other membrane bound proteins 5,6 . These observations underpin the intrinsic curvature hypothesis, which postulates that cells regulate the composition of their biological membranes so that the net curvature elastic stress is under homeostatic control [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, curvature elastic stress, which arises from a system being forced to adopt a curvature that is different from c 0 , has been shown to modulate the activity of many membrane interacting proteins 3,4 and drives the folding of other membrane bound proteins 5,6 . These observations underpin the intrinsic curvature hypothesis, which postulates that cells regulate the composition of their biological membranes so that the net curvature elastic stress is under homeostatic control [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors did not find any significant effect of water temperature on the PUFA levels in fish in a laboratory or in natural waters [18,[57][58][59][60][61]. Moreover, in many works the putative peculiar role of EPA or DHA in the temperature adaptations of the cell membrane properties (fluidity, order, curvature and elastic stress) was not confirmed [53,58,[62][63][64]. In any case, in our study water temperature in the subarctic water bodies was below 16 °C and hardly contributed considerably to the observed differences in EPA and DHA contents between the studied species.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, Arts et al [54] found that under a laboratory conditions an increase of water temperature from 12 to 19 °C caused a decrease of DHA content in juvenile Atlantic salmon (Salmo salar) from 4.6 to 3.3 mg g −1 wet weight (recalculated from dry weight using mean moisture content in Salmoniformes 72.5%). Moreover, in many works the putative peculiar role of EPA or DHA in the temperature adaptations of the cell membrane properties (fluidity, order, curvature and elastic stress) was not confirmed [53,58,[62][63][64]. However, other authors did not find any significant effect of water temperature on the PUFA levels in fish in a laboratory or in natural waters [18,[57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, membrane fluidity or membrane viscosity, in addition to the degree of unsaturation, strongly depends on the type of lipid head-groups as well as the presence of another lipid species, cholesterol (Arts and Kohler 2009;Dymond 2016). Therefore, the notion that the differences in DHA contents between species are dictated by temperature-dependent membrane fluidity needs is simplistic (Infanteet al 2001).…”
Section: Water Temperaturementioning
confidence: 99%